Converting rubber seed oil into hydrocarbon fuels via supported Pd-catalyst - Yubao, Chen; Yajie, Hao; Yongyan, Zhao; Liming, Zhou; Shunping, Yang; Yanni, Gao; Jiangli, Ma; Junchen, Du; Souliyathai, Dona; Aimin, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
The one-step hydrotreatment of rubber seed oil to produce hydrocarbon fuels has been carried out via supported Pd-catalyst, and analyzed emphatically some elements affected catalytic cracking process, for example, temperature, hydrogen partial pressure and dosage of catalyst, etc. Through experimental research, the author found out the appropriate catalytic cracking conditions as follows: 310°C of reaction temperature, 2 MPa of hydrogen partial pressure, 15 of the ratio of oil to catalyst (m(oil)/m(catalyst)), 100 r/min of stirring speed. Under these conditions, effective component of hydrocarbon fuels in the converted oil accounts for 99.49%, and the proportion of C8-C16 can reach as high as 79.61%. The converted oil was similar to petroleum-based oil in chemical composition, and can be used for future the aviation biofuels development as the source of raw material because it contains a large amount of hydrocarbon in the range of C8-C16. Keywords: rubber tree seed oil, catalytic cracking, Pd based catalyst, hydrocarbon fuels, biofuel, renewable energy DOI: 10.25165/j.ijabe.20171006.2742 Citation: Chen Y B, Hao Y J, Zhao Y Y, Zhou L M, Yang S P, Gao Y N, et al. Converting rubber seed oil into hydrocarbon fuels via supported Pd-catalyst. Int J Agric & Biol Eng, 2017; 10(6): 201–209.